2013
DOI: 10.1111/hsc.12085
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of persons in the work environment to the self-identity of persons with mental health problems: a study in Israel

Abstract: This study explores the contribution of others in the workplace to the self-identity and job integration of persons with severe mental health problems. Thematic content analysis of in-depth, semi-structured interviews conducted in 2009 with 15 Israelis with severe mental health problems who work in a variety of frameworks (protected and supported employment and open market) revealed three main themes: (i) dissatisfaction with the protected work settings in which they were initially employed; (ii) the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In this sense, it is suggested that by being a contributive member of society, persons in recovery working as peer providers may cultivate their "internal strength" and reconstruct a sense of self which further promotes their recovery process (Auerbach & Richardson, 2005). Similar processes are evident among the nonclinical sample which demonstrate the versatility of human capability to grow above and beyond given adverse circumstances and develop a sense of meaning, efficacy, fulfillment, and self-worth (e.g., Baum & Neuberger, 2014;Bond, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it is suggested that by being a contributive member of society, persons in recovery working as peer providers may cultivate their "internal strength" and reconstruct a sense of self which further promotes their recovery process (Auerbach & Richardson, 2005). Similar processes are evident among the nonclinical sample which demonstrate the versatility of human capability to grow above and beyond given adverse circumstances and develop a sense of meaning, efficacy, fulfillment, and self-worth (e.g., Baum & Neuberger, 2014;Bond, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties integrating into work for individuals with psychiatric disorders are especially flagrant in discriminatory workplaces characterized by unsupportive relationships with coworkers and supervisors [21]. According to Baum & Neuberger [28] individuals with a mental illness consider their social support at work, namely with supervisors and coworkers, as essential for helping them integrate at work. Other studies also report that significant relationships at work and social encouragement are leading factors in facilitating the work integration of people with mental disorders [29][30][31], as well as their job satisfaction [32].…”
Section: The Relationship Between Social Support and Work Productivitymentioning
confidence: 99%
“…The importance of work as a cultural practice has been recognized by many researchers, some specifically oriented towards studying the meaning of work for people with mental illness [22,25,26]. Work provides the power to access new and further material and cultural elements, and the corresponding sense of independence and satisfaction in gaining that power through socially recognized productivity.…”
Section: Qualitative Research About Employment Barriers and Facilitatorsmentioning
confidence: 99%
“…People with mental health-related disabilities, who commonly have difficulty in obtaining and keeping a job, and who are in situations of strong economic and social dependence, probably give more importance to work and to the benefits obtained from it. Working is fundamental for people with a psychiatric disability because it provides an occupation and stable daily organization, with a clear definition of the difference between work time and leisure time [22,25,26]. Access to new work and leisure practices and relationships strengthens people's social identity and allows them to recognize themselves with that positive sense of satisfaction provided by the work activity.…”
Section: Qualitative Research About Employment Barriers and Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation